Labdane diterpenoids from Forsythia suspensa with anti-inflammatory and anti-viral activities. (May 2020) - Xiang, Kang-Lin; Liu, Rong-Xia; Zhao, Lin; Xie, Ze-Ping; Zhang, Shu-Min; Dai, Sheng-Jun
Abstract: Five previously undescribed labdane diterpenoids, named Forsypensins A-E, were isolated from the fruits of Forsythia suspensa . The structures and relative configurations of the compounds were elucidated via extensive spectroscopic methods, and their absolute configurations were fully confirmed by single crystal X-ray diffraction analyses using Cu Kα radiation and electronic circular dichroism data. The five labdane diterpenoids showed in vitro anti-inflammatory activity in rat polymorphonuclear leukocytes, inhibiting the rates of β -glucuronidase release by 43.6%–49.2% at concentrations of 10  μ M. The compounds also had anti-viral activity against influenza A (H1N1) virus and respiratory syncytial virus (RSV), with IC50 values in the range 21.8–27.4  μ M, and EC50 values in the range 10.5–15.4  μ M, respectively. Graphical abstract: Image 104160 Highlights: Five undescribed labdane diterpenoids were isolated from the fruits of Forsythia suspensa. The discovery of undescribed labdane diterpenoids is a further illustration to the diverse constituents of Forsythia. Five undescribed labdane diterpenoids were found to show anti-inflammatory and anti-viral activities.